Recent Advances in Hydroponic Culture Media Composition and Their Effect on Plant Growth - Aggarwal, Akanksha; Mathur, Ashwani (Defence Life Science Journal, 2023)
The growing demand for food resources is facing a shortage of supplies subject to the reduction in cultivable land globally, and a dire need for alternative cultivation strategies is the need of the hour.Scientists and researchers throughout the world are focusing onalternative cultivation strategies. However, this kind of cultivation is scarce in developing countries, including India, where the impact is paramount and will woo offthe growing population and reduce cultivable land, as per land census data (2020).Hydroponics isa robust solution forgrowing plants under controlled and regulated cultivation conditions.The term hydroponics means the water at work, which primarily focuses on giving specific nutrientsto support the growth and development of the plant.This opens floodgates for researchers to formulate and optimize novel nutrient growth media.Agricultural output has been duly enhanced with this multifaceted intensive technique.Marketing research data projects that thehydroponics market will be 12,000 million US dollars by 2025.The nutrient solutions are designed to provide all essential macro and micronutrients to plants.The well-aerated media with essential nutrients, crucial organic salts, and balance of ionic concentration, conductivity, and pH, is vitalfor hydroponic culture, a solution to redundant environmental concerns.The current review highlights recent advances in the optimization of hydroponic media compositions.The synergistic effects of a multitude of media on plant growth and product yield have been discussed.